Biochar-bacteria partnership improves rice growth and soil microbial community diversity while decreasing antimony accumulation and in-vitro bio-accessibility in contaminated soil - Muhammad Umair Hassan; Lorenzo Barbanti; Luigimaria Borruso; Paola Mattarelli; Monica Marianna Modesto; Huang Guoqin; Duan Renyan; Haiying Tang; Faizah Amer Altihani (Environmental Chemistry and Ecotoxicology)
Antimony (Sb) is a toxic metalloid impacting on plants, humans and ecosystem stability. Biochar (BC) is a promising amendment to mitigate toxic metals/metalloids. However, the role of BC and bacterial inoculation in mitigating Sb toxicity and bio-accessibility, and reshaping soil bacterial community has not yet been explored. To investigate this subject, a rice pot experiment was set up involving six treatments: unstressed soil (Ctrl); 1200 mg Sb kg−1 (Sb stress); Sb stress +1 % BC (1 % BC); Sb stress +2.5 % BC (2.5 % BC); Sb stress +1 % BC + Bacillus subtilis bio-inoculum (1 % BC + BI); Sb stress +2.5 % BC + BI (2.5 % BC + BI). The serious impairment in rice growth, physiology and final yield determined by Sb stress was reduced by BC and associated BI. The maximum stress relief was obtained with 2.5 % BC + BI, which increased rice growth and final grain yield (+85 %) by improving several plant traits and soil properties, while decreasing Sb availability. 2.5 % BC + BI curbed Sb concentration in plant organs (−43 % in the whole plant), whereas Sb whole plant content was moderately reduced (−13 %), due to a growth driven Sb uptake effect. Upon 2.5 % BC + BI, soil total Sb concentration and in vitro bio-accessibility were similarly reduced (average, −35 %) due to increases in soil total carbon (+61 %), microbial biomass carbon (+37 %), and enzymatic activities (+72 % in the average of urease and catalase). The addition of BC + BI significantly boosted the relative abundance of soil bacteria involved in reducing Sb toxicity. Our findings highlight BC + BI potential to improve rice production, reduce Sb plant accumulation, soil in-vitro bio-accessibility, and ameliorate soil bacterial community diversity.